A rare case: A giant right coronary artery aneurysm mimicking a paracardiac mass - Güneş, Yasin Celal; Parlak, Selçuk; Yurduseven Çıvgın, Esra; Eren, Serhan; Çayhan, Velihan; Beşler, Muhammed Said (Journal of Surgery and Medicine, 2022)
Giant coronary artery aneurysms are extremely rare pathologies that can be confused with paracardiac and mediastinal masses, which are usually diagnosed incidentally. In this case report, an 83-year-old patient with a 70x35 mm thrombosed right coronary artery aneurysm misdiagnosed as a paracardiac mass will be discussed in light of the literature.